Diagnosis of Dengue Virus Infection in Oral Fluid using Immunochromatographic Tests. (Bangladesh Journal of Medical Microbiology, 2017)
Dengue viral infections are diagnosed by detecting dengue NS1 antigen and dengue specific IgM/IgG antibody by traditional serological tests using patient's blood. Recently saliva is being used employed for diagnosis of different infectious diseases including dengue. In the present study, dengue NS1 antigen and anti-dengue IgM/IgG antibody were detected using rapid immunochromatographic (ICT) kits for diagnosis of dengue and compared with the results of serum ICT results performed on corresponding sera collected from the same individuals. A total of 215 suspected dengue patients were tested and dengue infection was found in 176 (81.9%) sera and 161 (74.9 %) oral fluid samples. Among the 30 dengue NS1 antigen positive sera, 28 were also positive for NS1 in oral fluid indicating high sensitivity (93.3%), specificity (100%), diagnostic accuracy (99.1%), PPV (100%) and NPV (98.9 %) of testing dengue NS1 antigen in oral fluid. Similarly oral fluid assay for anti-dengue IgM showed sensitivity, specificity, diagnostic accuracy, PPV and NPV of 87.3%, 100.0%, 95.8%, 100.0% and 94.1% respectively. Test for anti-dengue IgM/IgG in oral fluid showed sensitivity, specificity, diagnostic accuracy, PPV and NPV of 89.7%, 100.0%, 98.1%, 100.0% and 97.7% respectively. All these parameters for detection of anti-dengue IgG by ICT showed 100%in oral fluid. Thus, results from this study indicates that detection of dengue NS1 antigen or anti-dengue IgM/IgG in oral fluid is an alternative tool for dengue diagnosis. It may benefits dengue diagnosis especially in infants and children since it is easy to collect and require no additional sample processing. It also has the potential to use for epidemiological survey.Bangladesh J Med Microbiol 2017; 11 (1): 6-9